MENINGKATKAN HASIL BELAJAR AGAMA ISLAM PADA MATERI SIFAT WAJIB BAGI ALLAH SWT MENGGUNAKAN MODEL PEMBELAJARAN WORD SQUARE DI KELAS III SDN 117/ III KOTO DATUK KECAMATAN AIR HANGAT KABUPATEN KERINCI - Romi Yilhas (Ensiklopedia Education Review, 2021)
: Learning is a planned activity carried out in order to improve the knowledge and understanding of students, this study aims to find out what efforts can be made to improve Islamic learning outcomes (PAI) using the word square method at SDN 117/III Koto Datuak District Air Warm Kerinci, This research is a classroom action research that aims to improve PAI learning outcomes in the classroom. The research subjects were third grade students, who had the lowest learning outcomes. The research was conducted in three cycles. Each cycle uses a Kemmis and Taggart research model or design which consists of four components, namely planning, acting, observing, and reflecting. The data collection technique used the learning outcomes test technique, where there were two learning outcomes tests, namely pretest and posttest. The test in this study used a formative test in the form of an objective test, the test questions were realized in the form of multiple choice. The data analysis technique is by comparing the average (mean) results of the learning test before and after the action is taken. The results showed that the word square method could improve PAI learning outcomes with indicators, there was an increase in the average PAI learning outcomes from the pretest results of 70.06 increased to 73.91 in the first cycle, increased again to 76.79 in the second cycle and increased again to 78.94 in cycle III. The achievement of KKM physically also increased from the pre-cycle of 36.36% to 60.61% in the first cycle, increased again to 72.73% in the second cycle and increased again to 81.82% in the third cycle. This means that there has been a significant increase in results in cycle III, so the word square method can be standardized into a model to improve PAI learning outcomes.Keywords: Learning Outcomes of Islam, Mandatory Traits for Allah, Word Square Model.